On the integer solutions of the Pell equation \(x^2=13y^2-3^t\) - Gopalan, M.A.; Sangeetha, V.; Somanath, Manju (International Journal of Applied Mathematical Research, 2014)
The binary quadratic Diophantine equation represented by is considered and analyzed for its non-zero distinct integer solutions for the choices of tÂ given by (i) \(t=1\) (ii) \(t=3\) (iii) \(t=5\) (iv) \(t=2k\) and (v) \(t=2k+5\). A few interesting relations among the solutions are presented. Further, recurrence relations on the solutions are obtained.Keywords: Pell equation, integer solutions of Pell equation, binary quadratic Diophantine equation.